2018
DOI: 10.3390/molecules23061414
|View full text |Cite
|
Sign up to set email alerts
|

Prussian Blue Nanoparticles as a Versatile Photothermal Tool

Abstract: Prussian blue (PB) is a coordination polymer studied since the early 18th century, historically known as a pigment. PB can be prepared in colloidal form with a straightforward synthesis. It has a strong charge-transfer absorption centered at ~700 nm, with a large tail in the Near-IR range. Irradiation of this band results in thermal relaxation and can be exploited to generate a local hyperthermia by irradiating in the so-called bio-transparent Near-IR window. PB nanoparticles are fully biocompatible (PB has al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 89 publications
2
65
0
Order By: Relevance
“…S1; c and d) and pristine ( Fig. S1; g and h), the cuboidal nature of the PB at the 2× dipped cycles for the treated GFA3 had given way to a more spherical PBNP as earlier reported [49]. This is most likely due to clustering, which forced the shapes to morph from cubes into more irregular shapes.…”
Section: Resultssupporting
confidence: 57%
“…S1; c and d) and pristine ( Fig. S1; g and h), the cuboidal nature of the PB at the 2× dipped cycles for the treated GFA3 had given way to a more spherical PBNP as earlier reported [49]. This is most likely due to clustering, which forced the shapes to morph from cubes into more irregular shapes.…”
Section: Resultssupporting
confidence: 57%
“…As a result, they are promising agents for photothermal therapy (PTT) for the treatment of several diseases, including cancer and bacterial infections. [27][28][29] Maaoui et al reported that PB NPs coated with polyvinyl pyrrolidone (PVP), in combination with near infra-red (980 nm) laser irradiation, can be used for the robust ablation of virulent Gram positive and Gram negative bacterial strains. 30 However, mechanistic details related to their interaction with the bacterial cells were not provided.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles (NPs) capable of relaxing thermally when irradiated at the wavelength of their absorption bands add interesting photothermal properties to the many peculiarities of matter at the nanoscale. NP of this kind are made of highly absorbing substances such as Prussian Blue [1], copper sulfide [2] or, more frequently, noble metals [3]. In the latter case, the absorption bands responsible of the photothermal effect are due to the well-known phenomenon of localized surface plasmon resonance (LSPR).…”
Section: Introductionmentioning
confidence: 99%